Interactions between drugs and polymers influencing hot melt extrusion. (11th December 2013) - Li, Yongcheng; Pang, Huishi; Guo, Zhefei; Lin, Ling; Dong, Yixuan; Li, Ge; Lu, Ming; Wu, Chuangbin
Abstract: Objectives: Hot melt extrusion (HME) as a technique for producing amorphous solid dispersion (ASD) has been widely used in pharmaceutical research. The biggest challenge for the application of HME is the thermal degradation of drug, poor physical stability of ASD and precipitation of drug during dissolution. Interactions between drugs and polymers may play an important role in overcoming these barriers. In this review, influence of drug–polymer interactions on HME and the methods for characterizing the drug–polymer interactions were reviewed. Key findings: Strong drug–polymer interactions, especially ionic interactions and hydrogen bonds, are helpful to improving the thermal stability of drug during HME, enhancing the physical stability of ASD during storage and maintaining supersaturated solution after dissolution in gastrointestinal tract. The interactions can be quantitatively and qualitatively characterized by many analysing methods. Conclusions: As many factors collectively determine the properties of HME products, drug–polymer interactions play an extremely important role. However, the action mechanisms of drug–polymer interactions need intensive investigation to provide more useful information for optimizing the formulation and the process parameters of HME.